Firm Size As A Moderation Factor: Testing The Relationship of Capital Structure With Dividend Policy - Akhmadi Akhmadi; Bambang Mahmudi; Moh Muksin; Indra Suhendra; Rina F (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2020)
This study examines size as a variable that can strengthen and weaken the relationship between debt policy and dividend policy. Presearch using a sample of 26 companies of 65 population Basic industrial and chemical manufacturing companies listed on the Indonesia Stock Exchange in 2011-2015, which is determined by purposive technique. The variables observed include debt policy as an independent variable, dividend policy as the dependent variable, and firm size as a moderating variable. The analysis tool uses regression moderating analysis (MRA). The results prove that the Debt to Asset Ratio (DAR) has a negative and insignificant effect on the Dividend Payout Ratio (DPR), firm size negatively moderates and there is a significant relationship between capital structure and dividend policy.